Efficacy and safety of intracoronary epinephrine versus conventional treatments alone in STEMI patients with refractory coronary no‐reflow during primary PCI: The RESTORE observational study. Issue 4 (17th July 2020) - Navarese, Eliano P.; Frediani, Lara; Kandzari, David E.; Caiazzo, Gianluca; Cenname, Angela Marella; Cortese, Bernardo; Piva, Tommaso; Muçaj, Andi; Tumscitz, Carlo; Paparoni, Francesco; Larosa, Claudio; Bisceglia, Teodoro; et al.
Abstract: Objectives: We aimed to compare intracoronary (IC) epinephrine versus conventional treatments alone in patients with ST‐elevation myocardial infarction and refractory coronary no‐reflow during primary percutaneous coronary intervention (PPCI). Methods: Thirty consecutive patients with severe refractory coronary no‐reflow (TIMI 0–1, MBG 0–1) during PPCI were prospectively included after initial failure of conventional treatments. Conventional treatments used in both groups included IC nitrates, thrombectomy. Glycoprotein IIb/IIIa inhibitors and adenosine. Patients received IC epinephrine or no epinephrine. Results: Intracoronary administration of epinephrine yielded significantly better coronary flow patterns (28.6% TIMI 3, 64.3% TIMI 2, 7.1% TIMI 1, and 0% TIMI 0), compared to those after treatment with conventional agents alone (18.8% TIMI 3, 12.5% TIMI 2, 37.5% TIMI 1, and 31.3% TIMI 0) ( p value between groups = .004). In the IC epinephrine vs. no epinephrine group there was a significant reduction of 30‐day composite of death or heart failure (35.7% vs. 81.25%), improvement of ejection fraction ( p = .01) and ST‐segment resolution ( p = .01). Conclusions: The findings of this proof‐of‐concept study suggest that as compared to use of conventional agents alone, IC epinephrine provides substantial improvement of coronary flow in STEMI patients with refractory no‐reflow during PPCI that may result into improved prognosis.